Noções de física quântica a partir do estudo do funcionamento de dispositivos semicondutores – uma unidade de ensino potencialmente significativa para 3ª Série do Ensino Médio - Campos, Gustavo de Carvalho (2016)
The distance between research and methods of quantum physics in the classroom hasbeen attenuated by a group of teachers researchers committed to improving the qualityof education configured currently in Brazilian schools. The contents of Modern and Contemporary Physics are generally not targeted to basic education, either by lack ofteaching experience, the lack of time or by the students' difficulties. Thereby, a numberof publications suggest mainly the urgency to rethink the teaching of physics byproposing the inclusion these contents in the basic education. In our work, wedeveloped an UEPS (Unit of Teaching Potentially Significant) in order to present someconcepts of quantum physics from the problematization of a more general andinclusive content - the functioning of semiconductor devices. Much of the developmentof these electronic devices comes from the discoveries of physics of the last centuries,and therefore it is essential the inclusion of at least some of the topics in high school.We seek to bring an experience report on the implementation of this UEPS in a classof 3rd grade of high school. The intervention in the classroom took place in a publicschool in the city of Serrinha-BA. During the research was requested to the studentssolving questionnaires and elaboration of conceptual maps to obtain evidence ofMeaningful Learning of quantum physical's concepts. The criteria used for the dataanalysis was the aspects of Ausubel's theory as the progressive differentiation andintegrative reconciliation. Our results show that the UEPS contributed to the MeanfullLearning of various concepts of quantum physics as Quantization and Theory ofBands. We highlight the importance of construction of conceptual maps in findingmeaningful learning, evidenced by the tiering process of ideas. On the other hand wefind some barriers in the implementation of UEPS, especially with regard to extrinsicproblems, such as the permanence of students by the end of these classes.